Study of the potential of a voice synthesizer in the educational process of a child with ataxia - Ana Teresa Oliveira; António José Osório; Anabela Cruz Santos (Universidade Federal de Santa Maria (UFSM), 2014)
This case study examines the use of Information and Communication Technologies (ICT) in supporting Bia (a fictitious name), a child with Ataxia, included in a Support Unit for the education of students with multiple disabilities of a school in Braga, Northern Portugal. Bia presented total incapacity in speech and severe difficulties in fine motor coordination. Thus, this study presents the relationship between special educational needs and ICT through their interconnection. In addition, this research addresses and describes the intervention in terms of ICT and its integration into the curriculum and Bias's learning process. The integration process is reported in order to provide supporting products for augmentative and alternative communication.